Terras, poéticas e lutas nas margens do rio Ribeira de Iguape: modos quilombolas de conceituar e manejar o mundo - Santos, Alessandra Regina (2021)
This thesis examines how the Quilombola-riverine people who inhabit the Atlantic Forest region in Vale do Ribeira, in southern São Paulo State, draw places, relationships, practices and knowledges by using unique perceptions of life and death, land and water, strength and struggle. The goal is to reflect ethnographically on the movements those collectives perform with the Ribeira de Iguape River in order to understand the multiple human and nonhuman, visible and invisible lives that pass through its waters, as well as their strategies to (re)exist and shape places suitable for coexistence. In this setting, life and death cycles guide the conceptualization and management of places, marking bodies and forms of engagement in the fight for land and water. By following the contrasting images and conceptual links explained by my interlocutors throughout my fieldwork between the months of October 2017 and August 2019, this study proposes an ethnographic writing exercise that is able to reveal the political and cosmological forces along with the existential poetics involved in producing bodies, lands, persons, and struggles among those peoples.